PEMANFAATAN RESIDU PENGGUNAAN PUPUK ORGANIK DAN PENAMBAHAN PUPUK UREA TERHADAP HASIL JAGUNG PADA LAHAN SAWAH BEKAS GALIAN C - Setie Harieni; Slamet Minardi (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2013)
Title : Residual Effect of Organic Fertilizer Utilization and Addition of Urea Fertilizer on The Yield of Corn on The  C-Excavation  Paddy Soil. The purposes of this study were to determine the effect of organic fertilizer residues and addition of urea fertilizers in improving soil fertility in the C excavation paddy soil and the yield of corn (Zea mays, L). Research was conducted by using completely randomized design (CRD) single factor, consisting of six treatments, as follows, P0: Control, residue treatment of : inorganic fertilizer (P1), Cow manure (P2), Bokhasi fertilizer (P3), manure and inorganic fertilizer (P4), Bokhasi and inorganic fertilizer (P5). Urea fertilizer was added a quarter of recommended dose for each treatment residue. It was given twice, except for the control treatment, and repeated 4 times, and placed randomly. Observations of soil chemical properties comprising: soil pH, C-organic, BS, CEC and the N-total crop land, while parameters of the plants, including components of the growth and yield of corn, were also observed. The results showed that the residue of organic fertilizer and the addition of urea fertilizer were able to increase the fertility of the C-excavation paddy soil. It has been proved by the growth and yield of corn were increased, such as plant height, fresh and dry weight of plant, weight and girth of the highest cob. Residual treatment obtained from the treatment of organic and inorganic fertilizer showed significantly different with the addition of urea fertilizer, as compared to control, however it showed not significantly different to other treatments.